(3cJGH aj GdCOHs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3hHYO, aEfj deG bqjV Gddg efj ddCOH eLdj SeGJgG acGf eeG bjOJg ef GdZQQ, hGbJfjJg ef faGFS Jdc GdOQQ s
(3BNQgG (B:s
(3hdG Tc Cf GdeQA WYeI OgQg aeG HGdg jG hjMg jCef GdOgQG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQ GdLRA GdCChd GdbSe GdQGHY ef GdCQbGe (B1819-1821 (3COHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
Keywords: (3GdCOHs